Interpersonal differences between of the entropies of EEG, HRV, immunocytogram and leukocytogram - O Popadynets'; A Gozhenko; W Zukow; I Popovych (Kazimierz Wielki University, 2019)
Background. Previously, we have shown that in humans entropy of the normalized parameters of the HRV and SPD of loci of EEG significantly correlate with the entropy of Leukocytogram and Immunocytogram as well as parameters of immunity, which testifies to their modulating regulatory effects. This article is a direct extension of the previous one. Its purpose is the distribution of the observed contingent into groups that are homogeneous in terms of entropy of the HRV, EEG as well as Leukocytogram and Immunocytogram. Material and methods. In basal conditions in 37 men and 14 women with chronic pyelonephritis and cholecystitis in remission as well as without clinical diagnose but with dysfunction of neuro-endocrine-immune complex and metabolism, we recorded twice, before and after balneotherapy at the spa Truskavets', EEG ("NeuroCom Standard") and HRV ("Cardiolab+VSR"). In blood we determined relative content of components (RCC) of Immunocytogram (ICG) (T helper, T cytolytic, B and NK lymphocytes) and Leukocytogram (LCG) (Eosinophils, Stub and Segmentonucleary Neutrophils, Lymphocytes and Monocytes). Than we calculated for each locus of EEG and HRV as well as for ICG and LCG the Entropy (h) of normalized spectral power density (SPD) or RCC using Shannon's formula. Results. The method of cluster analysis is revealed that in members of the major cluster (60%), the entropy of EEG, HRV, ICG and LCG varies within the normal range (-0,5σ ÷ +0,5σ). The members of the next largest cluster (23%) are characterized by a moderately increased entropy of the SPD of EEG in conjunction with the normal entropy of the ICG and the moderately reduced entropy of HRV and LCG. The members of the third cluster (9%) noted a significantly lower entropy (negentropy) of the SPD in loci F3, F4, T3 and C4; in addition, there is a moderate decrease in the entropy of the LCG. Instead, members of the last cluster (8) noted the negentropy of SPD in paired loci Fp1 and Fp2, T5 and T6, T3 and T4, F7 and F8 as well as O1 and O2; in addition, there is a moderate decrease in entropy of the ICG. The entropy of other EEG locus as well as of HRV and LCG is within the normal range. Conclusion. The enropy of HRV and SPD of loci of EEG as well as ICG and LCG is characterized by a large variation, which corresponds to the known wide variance of parameters of the ICG and LCG, which are subordinate to the regulatory influences of the central and autonomic nervous system.